60-GHz Double-Layer Transmitarray Antenna Using Complementary Structure - An, Wenxing; Zhang, Xiaochi; Luo, Yu; Wang, Jian; Xiong, Lin (Frontiers in Physics, 2022)
A novel double-layer transmitarray element is presented at 60 GHz with linearly- and circularly-polarized characteristics. A planar frequency-selective structure using the complementary design is adopted to augment the element performance for millimeter-wave applications. By integrating two different types of structure, i.e. cross and slot type, the compensation phase range is extended effectively with a satisfactory transmission magnitude. A transmitarray prototype is fabricated and tested to verify this double-layer complementary design. The measured gain at 60.5 GHz is 33.1 dBi with an aperture efficiency of 42.15%. Low side-lobe and cross-polarization levels are obtained. The proposed double-layer complementary design can reduce the structure complexity effectively and offer a high aperture efficiency at a low cost, which can be a potential candidate for the millimeter-wave transmitarray.